A novel fatty acid mimetic with pan-PPAR partial agonist activity inhibits diet-induced obesity and metabolic dysfunction-associated steatotic liver disease - Cigdem Sahin; Jenna-Rose Melanson; Florian Le Billan; Lilia Magomedova; Thais A.M. Ferreira; Andressa S. Oliveira; Evan Pollock-Tahari; Michael F. Saikali; Sarah B. Cash; Minna Woo; Luiz A.S. Romeiro; Carolyn L. Cummins (Elsevier, 2024)
Objective: The prevalence of metabolic diseases is increasing globally at an alarming rate; thus, it is essential that effective, accessible, low-cost therapeutics are developed. Peroxisome proliferator-activated receptors (PPARs) are transcription factors that tightly regulate glucose homeostasis and lipid metabolism and are important drug targets for the treatment of type 2 diabetes and dyslipidemia. We previously identified LDT409, a fatty acid-like compound derived from cashew nut shell liquid, as a novel pan-active PPARα/γ/δ compound. Herein, we aimed to assess the efficacy of LDT409 in vivo and investigate the molecular mechanisms governing the actions of the fatty acid mimetic LDT409 in diet-induced obese mice. Methods: C57Bl/6 mice (6-11-month-old) were fed a chow or high fat diet (HFD) for 4 weeks; mice thereafter received once daily intraperitoneal injections of vehicle, 10 mg/kg Rosiglitazone, 40 mg/kg WY14643, or 40 mg/kg LDT409 for 18 days while continuing the HFD. During treatments, body weight, food intake, glucose and insulin tolerance, energy expenditure, and intestinal lipid absorption were measured. On day 18 of treatment, tissues and plasma were collected for histological, molecular, and biochemical analysis. Results: We found that treatment with LDT409 was effective at reversing HFD-induced obesity and associated metabolic abnormalities in mice. LDT409 lowered food intake and hyperlipidemia, while improving insulin tolerance. Despite being a substrate of both PPARα and PPARγ, LDT409 was crucial for promoting hepatic fatty acid oxidation and reducing hepatic steatosis in HFD-fed mice. We also highlighted a role for LDT409 in white and brown adipocytes in vitro and in vivo where it decreased fat accumulation, increased lipolysis, induced browning of WAT, and upregulated thermogenic gene Ucp1. Remarkably, LDT409 reversed HFD-induced weight gain back to chow-fed control levels. We determined that the LDT409-induced weight-loss was associated with a combination of increased energy expenditure (detectable before weight loss was apparent), decreased food intake, increased systemic fat utilization, and increased fecal lipid excretion in HFD-fed mice. Conclusions: Collectively, LDT409 represents a fatty acid mimetic that generates a uniquely favorable metabolic response for the treatment of multiple abnormalities including obesity, dyslipidemia, metabolic dysfunction-associated steatotic liver disease, and diabetes. LDT409 is derived from a highly abundant natural product-based starting material and its development could be pursued as a therapeutic solution to the global metabolic health crisis.